Genetic aberrations in iPSCs are introduced by a transient G1/S cell cycle checkpoint deficiency - Araki, Ryoko (Nat Commun, 2020)
A number of point mutations have been identified in reprogrammed pluripotent stem cells such as iPSCs and ntESCs. The molecular basis for these mutations has remained elusive however, which is a considerable impediment to their potential medical application. Here we report a specific stage at which iPSC generation is not reduced in response to ionizing radiation, i.e. radio-resistance. Quite intriguingly, a G1/S cell cycle checkpoint deficiency occurs in a transient fashion at the initial stage of the genome reprogramming process. These cancer-like phenomena, i.e. a cell cycle checkpoint deficiency resulting in the accumulation of point mutations, suggest a common developmental pathway between iPSC generation and tumorigenesis. This notion is supported by the identification of specific cancer mutational signatures in these cells. We describe efficient generation of human integration-free iPSCs using erythroblast cells, which have only a small number of point mutations and INDELs, none of which are in coding regions.